Ubezpieczenia ustawowe w PRL jako instytucja ubezpieczeń w gospodarce centralnie planowanej - Wójtowicz, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article concerns the issue of compulsory insurance known in the period of the Polish People’s Republic, which was created by the law itself — the so-called statutory insurance. The basic methods used are the legal-dogmatic method and the descriptive method, the study of legal literature, and the analysis of legal acts and jurisprudence, mostly of a historical nature. Statutory insurance functioned from the 1950s until the end of the 1980s in a centrally planned economy, being specific to the so-called socialist insurance. The insurance relationship concluded by the operation of law could exist in a monopoly situation — in the different categories of insurance there was only one state insurer. In the literature and jurisprudence of the time, the statutory insurance relationship was usually classified as a civil law relationship. Such an assessment, however, raises doubts due to the number of public-law elements occurring in this type of insurance. Statutory insurance was an artificial insurance element, serving fiscal purposes.
Keywords: umowa ubezpieczenia; ubezpieczenia ustawowe; ubezpieczenia obowiązkowe; gospodarka centralnie planowana